Regulatory Reform in Disability Admissions: Ensuring Procedural Justice at UIN Sunan Gunung Djati Bandung - Tati Patnasih (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This study is motivated by the absence of binding institutional standards for disability accommodation in the student selection process at Universitas Islam Negeri Sunan Gunung Djati Bandung, leading to inconsistent implementation, unchecked bureaucratic discretion, and violations of procedural justice and legal certainty. The gap between regulatory mandates and implementation practices reflects systemic governance problems in higher education public services. This research employs a qualitative policy analysis approach based on literature review, supported by secondary data from laws, academic journals, and institutional documents. The analysis is framed using institutional theory, procedural justice, and street-level bureaucracy, and evaluated through William N. Dunn’s scoring model to determine the most optimal policy alternative. Findings indicate that the absence of standardized accommodation regulations leads to inconsistent decisions, weak accountability, and increased risks of procedural injustice across selection stages. The discussion confirms that the core problem is structural rather than individual, requiring regulatory standardization and strengthened control systems. The study concludes that policy reform is necessary through binding institutional regulations to ensure service consistency. Therefore, it recommends implementing standardized selection policies integrated with a Single Source of Truth (SSOT) digital system to strengthen fairness, transparency, and accountability in disability student selection.